Odpowiedzi

2010-01-13T22:26:03+01:00
Z.1
a) |x-8|=3
x-8=3
x=3+8
x=11

b) I6-xI=1.5
6-x=1.5
x=1.5+6
x=7.5

c) Ix-4I=3.8
x-4=3.8
x=3.8+4
x=7.8

e)|x+6|=-2
x+6=-2
x=-2-6
x=-8

f) Ix+1I=-1
x+1=-1
x=-1-1
x=-2

g) Ix+¼I=½
x+¼=½
x=½-¼
x=²/₄ - ¼
x=¼

z.2
a)|x-7|<3
x-7<3 i x-7>-3
x<3+7 i x>-3+7
x<10 i x>4

b)|x-3|<7
x-3<7 i x-3>-7
x<7+3 i x>-7+3
x<10 i x>-4

c)|x+6|>1
x+6>1 lub x+6<-1
x>1-6 lub x<-1-6
x>-5 lub x<-7

d)|x+4|>4
x+4>4 lub x+4<-4
x>4-4 lub x<-4-4
x>0 lub x<-8

e)|9-x|<7
9-x<7 i 9-x>-7
x<7+9 i x>-7+9
x<16 i x>2

f)|5+x|>8
5+x>8 lub 5+x<-8
x>8-5 lub x<-8-5
x>3 lub x<-13

z.3
a) I7x-3I =2
7x-3=2
7x=2+3
7x=5
x=0.7

b)I9x+5I=4
9x+5=4
9x=4-5
9x=-1
x=-0.1

c)I⅖x+4I=6
⅖x+4=6
⅖x=6-4
⅖x=2
x=3

d)I6-⁷/₅xI=1
6-⁷/₅x=1
-⁷/₅x=1-6
-⁷/₅x=-5
-x=-5* ⁵/₇
-x=- ²⁵/₇
x=3.6

z.4
a)√(x-7)² + Ix-7I <5
√x²+49 + x-7 <5
x+7 + x-7 <5
2x <5
x<5/2
x<2½

b)√x²-4x+4 +(x-2)>3
x-2x+2 +x-2 >3
0>3 wyrażenie sprzeczne
1 5 1